Association of the CHA2D(S2)-VASc Score and Its Components With Overt and Silent Ischemic Brain Lesions in Patients With Atrial Fibrillation - Steiner, Fabienne; Meyre, Pascal B.; Aeschbacher, Stefanie; Coslovsky, Michael; Sinnecker, Tim; Blum, Manuel R.; Rodondi, Nicolas; Cereda, Carlo W.; di Valentino, Marcello; Wenger, Florence; Cussigh, Andrea; Krisai, Philipp; et al. (Frontiers in Neurology, 2021)
Background: Silent and overt ischemic brain lesions are common and associated with adverse outcome. Whether the CHA2DS2-VASc score and its components predict magnetic resonance imaging (MRI)-detected ischemic silent and overt brain lesions in patients with atrial fibrillation (AF) is unclear. Methods: In this cross-sectional analysis, patients with AF were enrolled in a multicenter cohort study in Switzerland. Outcomes were clinically overt, silent (in the absence of a history of stroke/transient ischemic attack (TIA)) and any MRI-detected ischemic brain lesions. Logistic regression analyses were performed to assess the relationship of the CHA2DS2-VASc score and its components with ischemic brain lesions. An adapted CHA2D-VASc score (excluding history of stroke/TIA) for the analyses of clinically overt and silent ischemic brain lesions was used. Results: Overall, 1,741 patients were included in the analysis (age 73±8 years, 27.4% female). At least one ischemic brain lesion was observed in 36.8% (clinically overt: 10.5%; silent: 22.9%; transient ischemic attack: 3.4%). The CHA2D-VASc score was strongly associated with clinically overt and silent ischemic brain lesions (odds ratio [OR] (95% confidence interval [CI]) 1.32 (1.17-1.49), p<0.001 and 1.20 (1.10-1.30), p<0.001, respectively). Age 65-74 years (OR 2.58; 95%CI 1.29-5.90; p= 0.013), age ≥75 years (4.13; 2.07-9.43; p<0.001), hypertension (1.90; 1.28-2.88; p= 0.002) and diabetes (1.48; 1.00-2.18; p= 0.047) were associated with clinically overt brain lesions, whereas age 65-74 years (1.95; 1.26-3.10; p= 0.004), age ≥75 years (3.06; 1.98-4.89; p<0.001) and vascular disease (1.39; 1.07-1.79; p= 0.012) were associated with silent ischemic brain lesions. Conclusions: A higher CHA2D-VASc score was associated with a higher risk of both overt and silent ischemic brain lesions.